Analysis of Liquidity, Leverage, and Activity Ratio on the Financial Profitability of Indonesian Telecommunications Industry - Hasbiah, H. (Manunggal Halim Jaya, 2022)
This study aimed to analyze the effects of liquidity, leverage, and activity on the profitability of telecommunications companies listed on the Indonesian stock exchange. The analytical method used in this study is multiple linear regression analysis, where the data is obtained from Indonesia Stock Exchange. The sample used in this study is telecommunications companies listed on the Indonesia Stock Exchange. This research approach is quantitative. The results obtained in this study show that liquidity, leverage, and activity have a significant effect on profitability. Partially, liquidity has a negative and significant effect on profitability, leverage has a negative and significant effect on profitability, while activity has a positive and significant effect on profitability. Firstly, for companies should increase the company profitability by reducing liquidity which can reduce company profits so that it can attract investors to invest in their companies and can also improve their financial performance. Second, for investors, in assessing a company, it is better to pay attention to other factors that affect the company's profitability, such as company size, company growth, and dividend policy. Thrid, for further researchers, it is hoped that further researchers will use a larger research sample and add other variables that can affect profitability.